Factors shaping supply-demand relations on the fruit and vegetable market in the light of the behavior of groups and producer organizations = Wpływ uwarunkowań relacji popytowo-podażowych na rynku owoców i warzyw na zachowanie grup i organizacji producentów owoców i warzyw - Czyżewski, Andrzej; Bieniek-Majka, Maryla; Czakowski, Dariusz (Zielona Góra: Faculty of Economics and Management Press)
The authors have addressed the question to what extent the functioning of groups and organizations of fruit and vegetable producers depends on the market situation, the authors presented the shaping of supply-demand relations on the fruit and vegetable market in Poland in 2008-2016. They drew attention to the decreasing area of land intended for horticultural crops, with the simultaneous increase in the size of supply.
Keywords: rynek owoców i warzyw; integracja; producenci owoców i warzyw; fruit and vegetable market; integration; fruit and vegetable producers